Synthesis and characterization of poly(L-lactide-co-ε-caprolactone) copolymers: Influence of sequential monomer addition on chain microstructure - K. Nalampang (2018)
A series of copolymers with various compositions were synthesized by one-step and two-step bulk ring-opening polymerizations of L-lactide (LA) and ε-caprolactone (CL) using stannous octoate [Sn(Oct)2] and 1-hexanol as he initiating system. For the sequential two-step polymerization, a poly(ε-caprolactone) (PCL) prepolymer was polymerized first to a percent conversion of approximately 70% and LA then added in order to produce a copolymer with a chain microstructure different from that obtained from the corresponding one-step reaction. The resulting copolymers were characterized using a combination of nuclear magnetic resonance spectroscopy (1H- and 13C-NMR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and gel permeation chromatography (GPC). The average sequence lengths of the lactidyl (lLLe) and caproyl (lcape) units, the degree of randomness (R) and the transesterification coefficient (T(II) were calculated from the 13C-NMR spectra. The appearance of a signal due to CapLCap sequences was directly attributable to transesterification of lactidyl (LL) units. It was found that both lLLe and lcape values from the two-step syntheses were significantly longer than from the corresponding one-step syntheses, leading to different semi-crystalline morphologies and chain microstructures. The copolymers all showed at least some blocky chain structure as a result of the significant difference in monomer reactivity (LA > CL) between LA and CL. Thermal properties including stability depended on both composition and chain microstructure which could be controlled by the method of synthesis. From their DSC curves, the two-step copolymers were seen to be semi-crystalline whereas the one-step copolymers were mainly amorphous. A more blocky microstructure, as obtained from the two-step method, appeared to result in a lower thermal stability. Copyright © 2007 John Wiley & Sons, Ltd.